Shields-Harary numbers of graphs with respect to continuous concave cost functions - John Holliday; Peter Johnson (International Journal of Mathematics and Mathematical Sciences)
The Shields-Harary numbers are a class of graph parameters that measure a certain kind of robustness of a graph, thought of as a network of fortified reservoirs, with reference to a given cost function. We prove a result about the Shields-Harary numbers with respect to concave continuous cost functions which will simplify the calculation of these numbers for certain classes of graphs, including graphs formed by two intersecting cliques, and complete multipartite graphs.